Karakteristik Protein dan Struktur Jaringan serta Steroid Ikan Sidat (Anguilla bicolor bicolor) Berdasarkan Lokasi Daging Berbeda: Characteristics of Protein and Tissue Structure and Steroids Eel Fish (Anguilla bicolor bicolor) Based on Different Meat Locations - Mala Nurilmala; Agoes Mardiono Jacoeb; Yanti Sinaga; Agus Oman Sudrajat; Tatag Budiardi; Ronny Irawan Wahju; Mohammad Mukhlis Kamal; Ridwan Affandi; Rizsa Mustika Pertiwi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2022)
Eel is a consumable fish that has a unique taste and is rich in vitamins A, B1, B2, B6, C, D, protein albumin, DHA and EPA which is better known for omega-3, as well as its mineral content. This research aimed to determine the protein and steroid content and tissue structure in various parts of the body in eel fish (Anguilla bicolor bicolor). Eels are analyzed on three different body parts covering the front, central, and back. The protein profile was identified by the SDS-PAGE and Bradford methods, steroids by extraction method, tissue structure by the microscopic method. SDS-PAGE analyzed on eel fish meat has a protein molecular weight ranging from 9.825–199.196 kDa. Dissolved protein levels at the front, central, back are 0.307±0.02 mg/mL, 0.298±0.00 mg/mL, and 0.349±0.05 mg/mL. Water soluble and salt soluble proteins at the front, central, back are 0.469±0.01 mg/mL, 0.336±0.03 mg/mL, 0.437±0.00 mg/mL and 1.571±0.16 mg/mL, 1.312±0.11 mg/mL, 1.242±0.11 mg/mL. Eel fish contained steroids in ethyl acetate solvents. The structure of meat tissue and eel fish skin contained muscle fiber and stratum compactum layer.